Pengaruh Modifikasi Media Karet Gelang dalam Pembelajaran Atletik Nomor Lompat Tinggi Gaya Gunting pada Masa Pandemi Covid-19 - Ikbal Maulana Yusup; Citra Resita; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine whether modification of rubber band media had an effect on athletic learning in the scissor-style high jump number during the COVID-19 pandemic. This research is included in quantitative research using the experimental method of one group pre-test-posttest design. The population in this study amounted to 74 students and the sample used was 24 students, in this study the instrument used was a scissor style high jump technique skill test instrument. based on the results obtained in the study, the minimum value = 60, the maximum value = 80, the average value = 71.04, standard deviation = 6.590, and variance = 43,433 and the increase in students is as follows; (1) intervals 1-8 fall into the very low category totaling 0 students 0%; (2) intervals 9-12 fall into the low category totaling 4 students 17%; (3) intervals 13-16 are categorized as good enough with 20 students 83%; (4) interval 17-20 is in the very good or high category as many as 0 students 0%. This means that there is an increase in the 13-16 interval class in the fairly good category of 29% in the use of rubber band media modifications in learning athletic activities in the high jump number of students' scissors style.